Frontal Sinus Fractures - Schultz, Kelly; Braun, Tara L.; Truong, Tuan A. (Seminars in Plastic Surgery, 2017)
The frontal bone serves a protective role, representing the transition between the facial skeleton and the cranium. Within its enclosure, the frontal sinus lies adjacent to many important intracranial structures, and injury to this region has severe complications if not properly managed. Historically, the goals of frontal sinus fracture management have been to best prevent intracranial complications with invasive procedures, but a recent shift favoring conservative management now aims to preserve the form and function of the frontal sinus and its outflow tract. With the advancement of endoscopic techniques and the development of new technologies, many alternatives to aggressive surgical management are available.
Keywords: frontal sinus; facial fracture; nasofrontal tract; cranialization; endoscopic treatment